Maxillary premolars extraction or molar distalization with or without TADs: cephalometric evaluation of soft tissue changes in Class II treatment - Moser, Lorenz; Di Lorenzo, Enrica; Serafin, Marco; Maino, Giuliano; Schneider-Moser, Ute; Cozzani, Mauro; Caprioglio, Alberto (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2020)
Introduction: Problem solving in Class II malocclusion treatment performed with premolars extractions or distalizing techniques in relation to the profile modification.Aim: To cephalometrically compare soft tissue changes produced either by maxillary premolar extraction, tooth-borne Pendulum appliance or bone-borne MGBM appliance.Materials and Methods: Both pre- (T1) and post-treatment (T2) lateral cephalograms of 89 skeletal Class II patients (36 M, 53 F), treated during pubertal growth spurt, were retrospectively selected. Three groups were formed based on the therapy performed: 30 patients had been treated with maxillary first premolars extraction (U4), 31 patients with a conventional tooth-borne distalizing with Pendulum appliance (PA), and 28 patients with a skeletally anchored distalizing appliance (MGBM). Soft tissue was analyzed comparing upper (UL) and lower (LL) lip’s points with regard to True Vertical Line (TVL) and Esthetic plane (E-plane). Skeletal and dental values have been recorded in order to cephalometrically compare ΔT2-T1 changes among groups and to correlate dental and skeletal changes to profile modifications. One-way ANOVA was employed to compare groups at T1. Paired sample t-tests were employed to assess significant intra- and intergroup differences between T2 and T1. Significance level was set at 0.05Results: UL and LL showed a slight but not significant retrusion relative to TVL in all three groups. UL and LL distances to E-plane were not statistically significant among U4, PA, and MGBM groups. Independently of the treatment, UL was tangent to TVL in all groups. No statistically significant differences have been shown in skeletal records. Significant differences were recorded in Overjet among U4 than PA and MGBM groups.Conclusions: Class II malocclusion treatment with maxillary first premolar extraction, conventional or skeletal distalization did not significantly affect the profile producing similar changes in the soft tissue.